2008
DOI: 10.1029/2008gc002107
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle seismic structure beneath the Ethiopian hot spot: Rifting at the edge of the African low‐velocity anomaly

Abstract: [1] The Miocene-Recent East African Rift in Ethiopia subaerially exposes the transitional stage of rifting within a young continental flood basalt province. As such, it is an ideal study locale for continental breakup processes and hot spot tectonism. We combine teleseismic traveltime data from 108 seismic stations deployed during two spatially and temporally overlapping broadband networks to present detailed tomographic images of upper mantle P and S wave seismic velocity structure beneath Ethiopia. Tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
297
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(340 citation statements)
references
References 101 publications
41
297
2
Order By: Relevance
“…A similar broadening and westward shift in the location of the RVP anomaly is observed in the Rayleigh-wave phase-velocity maps of both Adams et al (2012) and O'Donnell et al (2013). The observation of low velocities at depth outside the rift valley and volcanic province is qualitatively similar to observations from the Main Ethiopian Rift (MER), where low velocities extend west beneath the Ethiopian Plateau at depths >75 km (Bastow et al 2008;Gallacher et al 2016). However, the absolute phase velocities are substantially lower (>5 per cent) within the MER (Gallacher et al 2016) at all periods compared to those in the Malawi Rift.…”
Section: The Rungwe Volcanic Province: the Localization Of Magmatism supporting
confidence: 69%
“…A similar broadening and westward shift in the location of the RVP anomaly is observed in the Rayleigh-wave phase-velocity maps of both Adams et al (2012) and O'Donnell et al (2013). The observation of low velocities at depth outside the rift valley and volcanic province is qualitatively similar to observations from the Main Ethiopian Rift (MER), where low velocities extend west beneath the Ethiopian Plateau at depths >75 km (Bastow et al 2008;Gallacher et al 2016). However, the absolute phase velocities are substantially lower (>5 per cent) within the MER (Gallacher et al 2016) at all periods compared to those in the Malawi Rift.…”
Section: The Rungwe Volcanic Province: the Localization Of Magmatism supporting
confidence: 69%
“…One per cent melt retention assumes strong melt-buoyancy effects, which have been previously proposed for mid-ocean ridges 21 and are also probably required beneath Afar. Previous surface-wave, body-wave and receiver-function results have similarly interpreted very slow velocities and very high V p /V s values as significant amounts of shallow melting 9,11,12 .…”
mentioning
confidence: 76%
“…Several recent seismic studies found evidence for melt in the crust and upper mantle beneath the rift based on high ratios of the P-wave velocity to the S-wave velocity (V p /V s ratios), velocities 5-10% slower than the global average and anisotropy [9][10][11][12][13] . However, precise determination of lithospheric thickness and depth of melting have proved challenging with existing seismic methodologies.…”
mentioning
confidence: 99%
“…In the case of Ethiopia, transition zone thickness, determined by receiver function analysis, shows evidence for thinning compared to the global mean; Cornwell et al (2011) cited this as evidence for high temperatures at transition zone depths, and thus connectivity between shallow low velocities imaged tomographically in Ethiopia (e.g., Bastow et al, 2008;Benoit et al, 2006;Debayle et al, 2001;Hansen et al, 2012;Pasyanos and Nyblade, 2007) and the superplume in the lower mantle beneath.…”
Section: Evidence From Broadband Seismologymentioning
confidence: 99%
“…The consensus emerging from recent studies in Ethiopia is that it is underlain by a broad low velocity anomaly, not a traditional narrow mantle plume (e.g., Bastow et al, 2008;Benoit et al, 2006;Cornwell et al, 2011;Hansen et al, 2012;Ritsema et al, 2010) (Fig. 5).…”
Section: Implications For the Thermochemical State Of The Ethiopian Mmentioning
confidence: 99%